Prevalence of periodontitis by Hispanic/Latino background among study participants of the Hispanic Community Cohort Study/Study of Latinos - Jiménez, Monik C. (J Am Dent Assoc, 2014)
BACKGROUND: Hispanics/Latinos are an ethnically heterogeneous population with distinct oral health risk profiles. Few studies have examined potential variation in the burden of periodontitis by Hispanic/Latino background. METHODS: A multicenter longitudinal population-based cohort study was used to examine the periodontal health status of 14,006 Hispanic/Latino adults 18–74 years at screening (2008 to 2011) who self-identified as Cuban, Dominican, Mexican, Puerto Rican, Central or South American from four US communities. Weighted, age standardized prevalence estimates and corrected standard errors of probing depth (PD), attachment loss (AL) and periodontitis classified per the CDC-AAP case definition are presented. A Wald Chi-square test was used to compare prevalence estimates across Hispanic/Latino background, age and sex. RESULTS: Over 51% of all individuals exhibited total periodontitis (mild, moderate or severe) per the CDC-AAP classification. Cubans and Central Americans exhibited the highest prevalence of moderate periodontitis (39.9% and 37.2%, respectively). Across all ages, Mexicans exhibited the highest prevalence of PD across severity thresholds. Among those 18–44 years, Dominicans consistently exhibited the lowest prevalence of AL at all severity thresholds. CONCLUSIONS: Measures of periodontitis varied significantly by age, sex and Hispanic/Latino background among the four sampled HCHS/SOL communities. Further analyses adjusted for demographic, systemic disease, and acculturation factors are needed. PRACTICAL IMPLICATIONS: Aggregating Hispanics/Latinos and/or applying estimates from Mexican Americans may substantially under- or over-estimate the burden of disease leading to errors in the estimation of needed clinical and public health resources. This information will be useful in informing decisions from public health planning to patient-centered risk assessment.